Role of Bacterial Cytoskeleton and Other Apparatuses in Cell Communication - Singhi, Divya; Srivastava, Preeti (Frontiers in Molecular Biosciences, 2020)
The bacterial cytoskeleton is crucial for sensing the external environment and plays a major role in cell to cell communication. There are several other apparatuses such as conjugation tubes, membrane vesicles and nanotubes used by bacterial cells for communication. The present review article describes the various bacterial cytoskeletal proteins and other apparatuses, the physical structures they form and their role in sensing environmental stress. The implications of this cellular communication in pathogenicity is discussed.